1994
DOI: 10.1007/bf01839256
|View full text |Cite
|
Sign up to set email alerts
|

Oxfendazole treatment of non-parasitized lambs and its effect on the immune system

Abstract: Ten parasite-free lambs were drenched with oxfendazole on days 0 and 28 and, one day after each drench, were injected with human erythrocytes and ovalbumin. Ten other antigen-injected lambs were not drenched (controls). Lymphocytes collected 3 days after each antigen injection and cultured in RPMI 1640 plus 5% fetal calf serum (FCS) and lymphocytes collected 3 days after the first and 3 and 7 days after the second antigen injection and cultured in 50% autologous serum had decreased blastogenic activity compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…However, this hypothesis is difficult to substantiate, given the low number of animals in the daily group and the lack of relevant clinical parameters on those animals that died. These results do parallel unexplained findings in a recent study in which oxfendazole-drenched lambs (two doses of 4.5 mg/kg) gained significantly more weight than the controls with no difference in levels of growth-promoting hormones (24). Increased intestinal parasite loads in the controls relative to treatment groups do not explain these weight gain differences, because the daily group weight gain was four times that of any other treatment group; monthly or weekly dosing should have effectively controlled intestinal parasites in these groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, this hypothesis is difficult to substantiate, given the low number of animals in the daily group and the lack of relevant clinical parameters on those animals that died. These results do parallel unexplained findings in a recent study in which oxfendazole-drenched lambs (two doses of 4.5 mg/kg) gained significantly more weight than the controls with no difference in levels of growth-promoting hormones (24). Increased intestinal parasite loads in the controls relative to treatment groups do not explain these weight gain differences, because the daily group weight gain was four times that of any other treatment group; monthly or weekly dosing should have effectively controlled intestinal parasites in these groups.…”
Section: Discussionsupporting
confidence: 88%
“…In another study, 2 of 10 sheep died of acute septicemia or pneumonia with bone marrow depression following daily treatment with albendazole (19). Recent work with oxfendazole in parasite-free lambs suggests that oxfendazole may depress humoral and cellular immunity even at much lower doses (4.5 mg/kg at 0 and 28 days) (24). Although the deaths of two of the sheep can be attributed to trauma, the most likely cause of the remaining deaths in the daily group remains immunosuppression secondary to the stress of daily dosing and inclement weather conditions, exasperated by the potential immunosuppressive effect of oxfendazole.…”
Section: Discussionmentioning
confidence: 99%
“…6 In direct contrast, others have shown that FBZ treatment of healthy mice attenuates the numbers of splenic CD4 + and CD8 + T cells. 7 In other species, treatment of healthy lambs reduces the ability of circulating lymphocytes to proliferate, particularly during secondary immune responses, 8,9 and FBZ has also been shown to block mitosis of cultured human lymphocytes. 10 These data suggest that FBZ may also affect aspects of mouse immunology.…”
mentioning
confidence: 99%
“…The older Romney lambs that were used in our experiment gave a protective response to the abbreviated infections. Another reason for the discrepancy could be the anthelmintic used, as OFZ has some stimulatory ability that could have helped the development of protective immunity in lambs (Stankiewicz et al 1994(Stankiewicz et al , 1996b. The protective response obtained seems primarily to operate at reducing the fecundity of H. contortus.…”
Section: Discussionmentioning
confidence: 99%